DOI: 10.17077/etd.d663cee3
|View full text |Cite
|
Sign up to set email alerts
|

Antedependence Models for Skewed Continuous Longitudinal Data

Abstract: A special thanks to my family. Words can not express how grateful I am to my parents for all of the sacrifices that you've made on my behalf. Your prayer for me was what sustained me thus far. I would also like to thank to my beloved husband, Dr. Tai-Hsuan Wu. Thank you for supporting me for everything, and especially I can thank you enough for encouraging me throughout this experience. To my beloved daughter Elena Wu, I would like to express my thanks for being such a good girl always cheering me up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
2
1
0
Order By: Relevance
“…Many studies have been carried out to assess the impacts of chlorine doses on THM formation. 27,60,86 Adin et al (1991) observed an increasing trend of THM formation with increasing chlorine dose and similar findings were reported in other works. 60,86 Adin et al (1991) also observed a lag in THM formation with a lower chlorine dose, which became more pronounced with a higher precursor concentration.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Many studies have been carried out to assess the impacts of chlorine doses on THM formation. 27,60,86 Adin et al (1991) observed an increasing trend of THM formation with increasing chlorine dose and similar findings were reported in other works. 60,86 Adin et al (1991) also observed a lag in THM formation with a lower chlorine dose, which became more pronounced with a higher precursor concentration.…”
Section: Resultssupporting
confidence: 80%
“…27,60,86 Adin et al (1991) observed an increasing trend of THM formation with increasing chlorine dose and similar findings were reported in other works. 60,86 Adin et al (1991) also observed a lag in THM formation with a lower chlorine dose, which became more pronounced with a higher precursor concentration. 27 The phenomenon could be explained by a dearth of chlorine to react with precursors, resulting in the formation of organochlorine intermediates rather than THMs.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation